Embedding a planar antiaromatic cyclooctatetraene into a truxene-derived polycyclic aromatic hydrocarbon - Ebel, Simone; Rominger, Frank; Mastalerz, Michael (Organic letters, 2025)
Two contorted, monkey saddle-shaped polycyclic aromatic hydrocarbons (PAHs) with tailored substitution patterns were synthesized to enhance their inversion barriers. Along the way, a chiral, truxene-based PAH featuring a planar cyclooctatetraene (COT) core was discovered and structurally confirmed by X-ray crystallography. Its antiaromatic character and optoelectronic properties were investigated and compared to those of its negatively curved precursor. Deuterium-labeling experiments and DFT calculations provided insights into the formation of the planar COT ring.
Gesehen am 10.11.2025